The Multi-Stimulus Box: An innovative learning device for the comparative study of object perception and recognition with various types of stimuli - Steurer, Michael Morten; Stephan, Claudia; Aringer, Josef; Berger, Wolfgang; Aust, Ulrike (Behavior Research Methods, 2012)
In this article, we report the construction of a novel type of automated learning device for exploring a broad range of issues in animal visual cognition. The testing box (Multi-Stimulus Box, or MSB) we describe is an experimental chamber that enables the flexible presentation of various stimulus types while providing control over incidental cues to the greatest possible extent. Among the stimuli that can be presented are photographs, real objects, and even holograms. The MSB allows for comparative research across different stimulus qualities and species, and is thus a promising tool for advancing our understanding of the role of stimulus qualities for animals’ perception, discrimination, and categorization of objects.<br
Keywords: Multi-Stimulus Box; Animal cognition; Holograms; Objects; Photographs